A perception of the look: the three paradigms of the image according to Peirce’s semiotic - Silva, Rosane (Comunicação & Educação, 2008)
Charles Peirce’s conceptions about Semiotic and his studies on thesubject about Perception to allow us reading at the images with a lot of creation shapes and we can cross this kind of the language with another expression way like ilimited possibility. Signs that produce itself to become known to the interpreter and it create a beehive that it gathers several interpretations way of seeing. And this support of the teories we are going to do the intersection analysis of the images in the poem called The princess Raga-Si,by José Arrabal.